Need Analysis of Critical Thinking Skills Acquisition through Adaptive Learning Model: Indonesian Perspective on Freedom of Learning Curriculum - Susilana, Rudi; Dewi, Laksmi; Setiawan, Budi; Alias, Norlidah; DeWitt, Dorothy; Hazar, Siti; Zulnaidi, Hutkemri (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to determine the needs of teachers at proposed schools using the freedom of learning curriculum to acquire the foundational principles of its curriculum acquisition within the learning, namely critical thinking and adaptive learning. The study's data were obtained using qualitative and quantitative research methodologies, including a scale designed by the researcher to evaluate teachers' needs for students' critical thinking completion through adaptive learning and semi-structured interview forms. The participants were junior high school teachers who taught at phase D (class VII-IX, ages 13- 15) in the total number of 123 people. The data were collected by using likert scale questionnaire and analysed by applying coding and key concepts techniques.  According to the findings, they require a focused revision for the main principles covering; critical thinking (interpretation, analysis, assessment, inferences, evaluation, explanation, self-reflection, inductive reasoning, deductive reasoning) and adaptive learning (students' behaviour, knowledge, achievement, preferences, information resources, navigational structure, trail generation, contents selection, goal selection) on the highly needed level.